2018
DOI: 10.1021/acs.langmuir.8b03627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Ionic Concentration on Nanodroplet Electrocoalescence

Abstract: Droplet electrocoalescence is of interest for various applications such as petroleum dehydration, electrospray ionization, and surface self-cleaning. Here, the effects of temperature and ionic concentration on nanodroplet electrocoalescence are investigated by molecular dynamics simulation. The results show that low ionic concentration rapidly drives ions towards water clusters and leads to dipole polarization of droplets. With an increase of ionic concentration, the particle–particle interaction is enhanced, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Several studies have been conducted employing MD simulations to explore the behavior of a nanometer-sized droplet in presence of electric fields, which include studies on electrowetting, droplet condensation, evaporation, electrocoalescence , of droplets, and droplet breakup . One of the pioneering works in this field by Daub et al consisted of an MD simulation study of the electrowetting phenomenon at the nanoscale wherein a succinct description of the electrowetting behavior for nanodroplets considered the fact that the number of molecules at the surface is relatively high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted employing MD simulations to explore the behavior of a nanometer-sized droplet in presence of electric fields, which include studies on electrowetting, droplet condensation, evaporation, electrocoalescence , of droplets, and droplet breakup . One of the pioneering works in this field by Daub et al consisted of an MD simulation study of the electrowetting phenomenon at the nanoscale wherein a succinct description of the electrowetting behavior for nanodroplets considered the fact that the number of molecules at the surface is relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…This calls for a comprehensive investigation in terms of different aspects that influence the wetting dynamics and statics of a nanoscale droplet in presence of electric field, and a number of these studies have utilized molecular dynamics (MD) simulations. 11,14,16,17 Several studies have been conducted employing MD simulations to explore the behavior of a nanometer-sized droplet in presence of electric fields, which include studies on electrowetting, 18 droplet condensation, 19 evaporation, 20 electrocoalescence 21,22 of droplets, and droplet breakup. 23 One of the pioneering works in this field by Daub et al 18 consisted of an MD simulation study of the electrowetting phenomenon at the nanoscale wherein a succinct description of the electrowetting behavior for nanodroplets considered the fact that the number of molecules at the surface is relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations on pure water droplet coalescence in the gas phase or on a super-hydrophobic surface to examine the coalescence-induced jumping were carried out. , Recently, our group has just studied the thermodynamics and dynamics of coalescence of pure water droplets . In addition to the case of pure water droplets, MD simulation studies on the coalescence of metal nanodroplets and electrocoalescence of conducting droplets were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…These hydrodynamic studies are very successful for understanding large droplets; however, for nanodroplets, molecular correlations and nanoscale interfacial effects become significant, the driving force is the specified molecular interaction, and the inhomogeneity of the fluids is at the molecular lever; in this case, macroscopic hydrodynamics is inapplicable. For nanoscale systems, molecular dynamics (MD) is one of the most popular methods . For example, Pothier et al used MD simulations to examine the coalescence of Cu and Si nanodroplets in three‐dimensional (3D), quasi‐two‐dimensional (quasi‐2D) and two‐dimensional (2D) spaces, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, in 2D space, coalescence is dominated by the inertial regime only. Chen et al used MD simulations to investigate how temperature and ionic concentration affect the coalescence of two nanodroplets. Chen et al found that a higher ion concentration and a lower temperature increased the effective particle‐particle interaction but decreased the mobility of the solvent, which resulted in a favorable ion concentration and favorable temperature for coalescence of a nanodroplet.…”
Section: Introductionmentioning
confidence: 99%